THE ANALYSIS OF MAJOR GRAMMATICAL ERRORS IN STUDENTS’ WRITING - Paramita, Paulina Erawati (Jurnal Pendidikan Bahasa, 2017)
This study investigates and classifies grammatical errors in writing made by year nine students at SMP Gembala Baik Bilingual Class. The samples of this research were 30 students randomly selected from 61 students. Descriptive qualitative was used to describe the errors made by the 30 students. They were asked to write about their holidays, and then the analysis was conducted to see the errors found in their writings. The results show that There were three errors inÂ noun endings,Â two errors in subject-verb agreement, four errors inÂ verb tense,Â four errors inÂ verb form, eight errors inÂ capitalization,Â six errors inÂ sentence fragment, andÂ two errors inÂ comma errors.Â The information of the types of studentsâ€™ errors can be used as a guidance to evaluate the weakness or progress of studentsâ€™ ability in learning English, particularly in writing. Keywords: grammatical errors, error analysis, contrastive analysis, English Â learning.